Relating Frontier Orbital Energies from Voltammetry and Photoelectron Spectroscopy to the Open‐Circuit Voltage of Organic Solar Cells. Issue 10 (28th January 2019) - Willems, Robin E. M.; Weijtens, Christ H. L.; de Vries, Xander; Coehoorn, Reinder; Janssen, René A. J.
Abstract: For 19 diketopyrrolopyrrole polymers, the highest occupied molecular orbital (HOMO) energies are determined from i) the oxidation potential with square‐wave voltammetry (SWV), ii) the ionization potential using ultraviolet photoelectron spectroscopy (UPS), and iii) density functional theory (DFT) calculations. The SWV HOMO energies show an excellent linear correlation with the open‐circuit voltage ( V oc ) of optimized solar cells in which the polymers form blends with a fullerene acceptor ([6, 6]‐phenyl‐C61 ‐butyl acid methyl ester or [6, 6]‐phenyl‐C71 ‐butyl acid methyl ester). Remarkably, the slope of the best linear fit is 0.75 ± 0.04, i.e., significantly less than unity. A weaker correlation with V oc is found for the HOMO energies obtained from UPS and DFT. Within the experimental error, the SWV and UPS data are correlated with a slope close to unity. The results show that electrochemically determined oxidation potentials provide an excellent method for predicting the V oc of bulk heterojunction solar cells, with absolute deviations less than 0.1 V. Abstract : To predict the open‐circuit voltage ( V oc ) of polymer–fullerene solar cells, three independent methods, square‐wave voltammetry (SWV), ultraviolet photoelectron spectroscopy, and density functional theory, are compared. For 19 diketopyrrolopyrrole polymers, SWV gives the best correlation. Remarkably, the slope of V oc with the blend's electrochemical gap is less than unity and possible reasons for this result are discussed.